1981
DOI: 10.1161/01.cir.63.3.527
|View full text |Cite
|
Sign up to set email alerts
|

The anatomic evolution of coronary artery disease demonstrated by coronary arteriography in 256 nonoperated patients.

Abstract: SUMMARY Coronary arteriography was performed twice in 256 nonoperated patients, including 92 surgical candidates who were recatheterized because of the long wait for surgery. Criteria to define progression and regression were established in advance. Analysis of separate segments, reflecting separate lesions, revealed that progression percentages increased proportionally with the degree of initial narrowing and the Interval between atheterizations, ranging from 1.2% to more than 20%. The highest progression per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(24 citation statements)
references
References 11 publications
4
20
0
Order By: Relevance
“…Less 'normal' coronary segments could mean less targets for the protective effect of nifedipine. The number of newly formed lesions was also highest in the RCA as already observed in previous studies [42][43][44]. One explanation may be that blood flow which has been shown to be different between the three large coronary arteries, could play a role in the development and progression of coronary atherosclerosis [45,46].…”
Section: Discussionsupporting
confidence: 67%
“…Less 'normal' coronary segments could mean less targets for the protective effect of nifedipine. The number of newly formed lesions was also highest in the RCA as already observed in previous studies [42][43][44]. One explanation may be that blood flow which has been shown to be different between the three large coronary arteries, could play a role in the development and progression of coronary atherosclerosis [45,46].…”
Section: Discussionsupporting
confidence: 67%
“…The number of atherosclerotic lesions, their distribution, length and degree of stenosis monitored during the procedure were found in both cohorts to be identical to the standard profile. 13 Moreover, the two patient groups did not differ with respect to their age (CHD: 54.3Ϯ7.2 years, nϭ174; no CHD: 54.9Ϯ7.7 years, nϭ158; range 34 to 64 years). As all patients included in the study were randomly selected, the group was typical in regard to CHD profile and indication for quantitative angiography with chest pain of unknown cause featuring most prominently in the CHD-free group of patients.…”
Section: Sample Collection and Diagnosis Of Chdmentioning
confidence: 88%
“…1 Previous studies have found no relation between coronary artery stenosis severity and risk of rapid progression, 2 but morphological features of coronary stenoses suggestive of increased plaque vulnerability have been reported to determine CAD progression. 2,3 In recent years, it has become apparent that both endothelial cell activation and monocyte/macrophage activation play a significant role in atherogenesis and plaque vulnerability and may determine rapid CAD progression.…”
mentioning
confidence: 96%